1999
DOI: 10.1302/0301-620x.81b2.0810255
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound screening for hips at risk in developmental dysplasia

Abstract: Between May 1992 and April 1997, there were 20 452 births in the Blackburn District. In the same period 1107 infants with hip 'at-risk' factors were screened prospectively by ultrasound. We recorded the presence of dislocation and dysplasia detected under the age of six months using Graf's alpha angle. Early dislocation was present in 36 hips (34 dislocatable and 2 irreducible). Of the 36 unstable hips, 30 (83%) were referred as being Ortolani-positive or unstable; 25 (69%) of these had at least one of the ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 19 publications
2
38
0
3
Order By: Relevance
“…This can be compared with 7.5% in the study by Holen et al (2002) in the group screened by the same process as in our study, and 18% in the study by Paton et al (1999). Thus, from this point of view it may be argued that our rate of delayed diagnosis was not unreasonably high.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…This can be compared with 7.5% in the study by Holen et al (2002) in the group screened by the same process as in our study, and 18% in the study by Paton et al (1999). Thus, from this point of view it may be argued that our rate of delayed diagnosis was not unreasonably high.…”
Section: Discussionsupporting
confidence: 60%
“…Congenital dislocation of the hip, defined as the application of orthopedic treatment, was diagnosed in 298 infants in our population of 19,820 screened babies (15 per 1,000). In comparison, Paton et al (1999) found a dislocation rate of 2.2 per 1,000, while Holen et al (2002) found 9.3 per 1,000. Rosendahl et al (1994) compared the effect of selective vs. general vs. no ultrasound screening for CDH on treatment rates.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Table 3 includes studies of population-based or primary care clinic-based cohorts screened by clinical examination as well as ultrasound screening that were published since the 1996 end point of the AAP review. 28,70,72,[80][81][82][83] Despite variation in the reference standards used in these studies, several important findings emerge. First, a high proportion of hips diagnosed with minor findings of dysplasia undergo spontaneous resolution.…”
Section: Use Of Imaging To Screen For Ddhmentioning
confidence: 99%
“…6,7 The guidelines stated that 60% of cases of DDH originated as a result of these risk factors, although this figure has been disputed. 8,9 Risk factors are currently thought to be associated with 30% to 31% of ultrasonographically-important DDH. 8,9 The National Screening Committee (UK) currently considers abnormalities of the foot to be a risk factor in DDH.…”
mentioning
confidence: 99%